Creating Graphitic Carbon Nitride Based Donor‐π–Acceptor‐π–Donor Structured Catalysts for Highly Photocatalytic Hydrogen Evolution. Issue 12 (12th February 2018) - Li, Kui; Zhang, Wei‐De
Abstract: Conjugated polymers with tailored donor–acceptor units have recently attracted considerable attention in organic photovoltaic devices due to the controlled optical bandgap and retained favorable separation of charge carriers. Inspired by these advantages, an effective strategy is presented to solve the main obstructions of graphitic carbon nitride (g‐C3 N4 ) photocatalyst for solar energy conversion, that is, inefficient visible light response and insufficient separation of photogenerated electrons and holes. Donor‐π–acceptor‐π–donor polymers are prepared by incorporating 4, 4′‐(benzoc 1, 2, 5 thiadiazole‐4, 7‐diyl) dianiline (BD) into the g‐C3 N4 framework (UCN‐BD). Benefiting from the visible light band tail caused by the extended π conjugation, UCN‐BD possesses expanded visible light absorption range. More importantly, the BD monomer also acts as an electron acceptor, which endows UCN‐BD with a high degree of intramolecular charge transfer. With this unique molecular structure, the optimized UCN‐BD sample exhibits a superior performance for photocatalytic hydrogen evolution upon visible light illumination (3428 µmol h −1 g −1 ), which is nearly six times of that of the pristine g‐C3 N4 . In addition, the photocatalytic property remains stable for six cycles in 3 d. This work provides an insight into the synthesis of g‐C3 N4 ‐based D‐π–A‐π–D systems with highly visible light response and long lifetime of intramolecular charge carriers for solar fuel production. Abstract : A graphitic carbon nitride‐based donor‐π–acceptor‐π–donor configuration is prepared by incorporating 4, 4′‐(benzoc 1, 2, 5 thiadiazole‐4, 7‐diyl) dianiline (BD) into g‐C3 N4 framework (UCN‐BD). BD acts as an electron acceptor, which endows UCN‐BD with narrow bandgap and a high degree of intramolecular charge transfer. The optimized UCN‐BD sample exhibits much superior performance for photocatalytic hydrogen evolution under visible light illumination (3428 µmol h −1 g −1 ).